Исследование колебаний вязкоупругих цилиндрических оболочек при малой вязкости - Курбанов, Н. Т.; Алиева, У. С. (НТУ "ХПИ", 2010)
У статті досліджується задача про коливання в'язкопружних циліндричних оболонок при малій в'язкості. Задача вирішується методом інтегрального перетворення Лапласа і рішення отримано у вигляді ряду, оригіналом перший члена якого є рішення аналогічної задачі, яке отримано методом усереднення. Отримане рішення досліджено для ядра Ржаніціна і показано вплив подальших членів на рішення.

The paper investigates the problem of vibration of viscoelastic cylindrical shells with low viscosity. The problem is solved by the method of integral Laplace transform and the solution is obtained in a series, the original of the first member of which is to solve a similar problem, which is obtained by averaging. The resulting solution is investigated for the kernel Rzhanitsina and shows the effect of subsequent terms of the decision.
Keywords: теория вязкоупругости; линейные вязкоупругие системы; преобразование Лапласа; вязкость материалов; колебания; линейная вязкоупругость